Preserving the Integrity of Organizations’ Quality Management System during Unification and Integration: Functional Approach - Marina V. Sokolovskaya; Elena V. Zamiralova (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
The article addresses the problems of preserving the integrity of quality management systems during integration of educational organizations into a single educational complex. The purpose of the article is to develop and test a functional approach of combining two educational organizations of different levels that preserves the integrity of existing quality management systems. The authors use methods of analysis, synthesis, generalization and comparison as well as system analysis, identification of cause-and-effect relationships, process and system approach, internal audits, self-assessment, expert assessment, ranking. The article considers the concept of integrity and related concepts. The authors propose a functional approach that uses several stages to maintain the integrity of quality management systems in compliance with all the rules for making changes to management systems and the principles of educational organizations integration. The approach is tested on a university and a college. The analysis identified the main categories of changes in organizations’ quality management system during integration and developed a synergetic model of the organization. The results can help improve the integrated quality management system in the future, not only in the field of education, but also in other areas of the economy.